Aesthetic refinement through intraoral excision: A Minimally Invasive Approach To Epidermoid Cyst Removal, A Case Report - Srivastava, Shamiksha; Chatterjee , Dipanjan; Tandon, Sapna; Chauhan, Himanshu; Mehra, Hemant; Tiwari, Garima (Journal of Neonatal Surgery, 2025)
Background Epidermoid cysts, also known as epidermal inclusion cysts, are benign, slow-growing lesions that often develop in the dermis. They arise from the hair follicles and are most commonly filled with keratinous material. Epidermoid cysts can occur anywhere on the body but are most often seen on the face, neck, and upper trunk. These cysts can vary in size and often present as small, firm, mobile, and non-tender nodules. Although usually asymptomatic, they can become infected or inflamed, causing pain and swelling [1]. Case Presentation This report presents a case of a 58 years old male patient with a cystic lesion in his right corner of mouth. The patient presented with a complaint of a painless, slowly enlarging nodule in the right side of the corner of the mouth. The lesion had been present for approximately 6 months, with gradual enlargement over time. The patient reported no associated symptoms, such as pain or discharge. Enucleation and excisional biopsy were carried out intraorally to avoid post-operative facial scarring. The specimen was sent to histopathology laboratory for evaluation, which suggested a confirm diagnosis of Epidermoid cyst. Conclusion Although Epidermoid cysts do not tend to recur, the need for regular follow-ups should not be underestimated, neither by the attending clinician nor by the patients themselves. In conclusion, the histopathologically proven and uneventful wound healing constitutes the only reassurance for the patient's well-being